An empirical assessment of the interactive impacts of irrigation and climate on farm productivity in Samarkand region, Uzbekistan - Sherzod Babakholov; Ihtiyor Bobojonov; Shavkat Hasanov; Thomas Glauben (Environmental Challenges, 2022)
Analyzing climate change's consequences is more complex for irrigated agriculture compared to rainfed. There are still limited researches that has considered the interactive effects of irrigation and climate variables regardless the fact that a broad range of climate studies was already involved in international literature. In this view, this study aimed at exploring the cross effects of irrigation with climate on farm output using ex-post assessment technique in Uzbekistan, where agriculture contributes for a large portion of the national GDP and irrigation water is becoming scarce. We applied a Stochastic Frontier Approach (SFA) with panel data from the central-eastern part of Uzbekistan for the period of 2013-2018, which includes a sample of 2,135 wheat and 1,141 cotton growers. The analysis revealed that climate factors have diverse influence by crop types across the region. Increased warming would be harmful for wheat farmers: a one-degree Celsius rise in average temperature between March and June could lead to up to 60% losses of total yields on wheat-growing farms, although precipitation has a positive significant effect. In contrast, increased temperatures are beneficial for cotton-growing farmers but excessive rainfall during the months of May-September could lead to 3% losses of total yields on cotton-growing farms. It's expected that both wheat and cotton growing farmers will suffer from temperature increases and excessive precipitation on their farms in the near future. More importantly, the interaction effects of irrigation and climate variables show that the cross effects of applied irrigation and mean temperature have highly significant positive impacts on the total yields of both wheat and cotton growing farmers in the study region. Thus, productivity in the region could be improved when enough water is available and more efficient irrigation techniques are used, otherwise declines in productivity could be witnessed.
Keywords: 330; agriculture; climate change; irrigation; panel data; Stochastic Frontier Approach (SFA)